New Mesomantispinae (Insecta: Neuroptera: Mantispidae) from the Jurassic of Karatau, Kazakhstan - Jepson, James E.; Khramov, Alexander V.; Ohl, Michael (Zootaxa, 2018)
Two new genera and species, and one indeterminate genera and species of fossil Mantispidae, Mesomantispinae are described from the Upper Jurassic of Karatau, Kazakhstan: Longicollum benmaddoxi gen. et sp. nov., Ovalofemora abbottae gen. et sp. nov., and Mesomantispinae sp. et gen. indet. Karataumantispa monstruosa is removed from the genus Karataumantispa and placed in the new genus Ovalofemora gen. nov. due to its different foreleg morphology (stout coxae, trochanter, and oval shaped femur), in addition to differences in wing venation. These taxa are all placed within the subfamily Mesomantispinae. An updated key to the genera of Mesomantispinae is given.